Tree plantations displacing native forests: The nature and drivers of apparent forest recovery on former croplands in Southwestern China from 2000 to 2015. (June 2018) - Hua, Fangyuan; Wang, Lin; Fisher, Brendan; Zheng, Xinlei; Wang, Xiaoyang; Yu, Douglas W.; Tang, Ya; Zhu, Jianguo; Wilcove, David S.
Abstract: China is credited with undertaking some of the world's most ambitious policies to protect and restore forests, which could serve as a role model for other countries. However, the actual environmental consequences of these policies are poorly known. Here, we combine remote-sensing analysis with household interviews to assess the nature and drivers of land-cover change in southwestern China between 2000–2015, after China's major forest protection and reforestation policies came into effect. We found that while the region's gross tree cover grew by 32%, this increase was entirely due to the conversion of croplands to tree plantations, particularly monocultures. Native forests, in turn, suffered a net loss of 6.6%. Thus, instead of truly recovering forested landscapes and generating concomitant environmental benefits, the region's apparent forest recovery has effectively displaced native forests, including those that could have naturally regenerated on land freed up from agriculture. The pursuit of profit from agricultural or forestry production along with governmental encouragement and mobilization for certain land uses – including tree planting – were the dominant drivers of the observed land-cover change. An additional driver was the desire of many households to conform with the land-use decisions of their neighbors. We also found that households' lack of labor or financial resources, rather than any policy safeguards, was the primary constraint on further conversion of native forests. We conclude that to achieve genuine forest recovery along with the resulting environmental benefits, China's policies must more strongly protect existing native forests and facilitate native forest restoration. Natural regeneration, which thus far has been grossly neglected in China's forest policies, should be recognized as a legitimate means of forest restoration. In addition, social factors operating at the household level, notably the pursuit of profit and conformation to social norms, should be harnessed to promote better land-cover, biodiversity, and environmental outcomes. More generally, for China and other countries to succeed in recovering forests, policies must clearly distinguish between native forests and tree plantations.